Fulminant skin GvHD with a cytokine pattern resemblant of cytokine release syndrome successfully treated with multimodal immunosuppression including tocilizumab. Issue 11 (7th July 2015) - Hellwig, Yuliya; Yoo, Young E.; Reß, Marie L.; Andres, Oliver; Braun, Matthias; Schlegel, Paul G.; Wölfl, Matthias
<x xml:space="preserve">Abstract</x> Acute Graft‐versus‐Host‐Disease (GvHD) is a potentially life‐threatening complication after allogeneic stem cell transplantation. If not treated early and adequately, the complex immunological mechanisms may lead to a self‐perpetuating cycle of alloreactivity, which is then associated with a high mortality. Here we assessed the cytokine profile on a daily basis in a patient with grade 4 skin GvHD, demonstrating a signature resembling cytokine‐release‐syndrome. After multimodal immunosuppressive intervention, including treatment with the IL6 receptor‐blocking antibody tocilizumab, the severe clinical symptoms unexpectedly resolved within 48hr. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.